Wearable Wireless Devices - Heidari, Hadi; Abbasi, Qammer Hussain; Alomainy, Akram (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
With the growing interest in the use of technology in daily life, the potential for using wearable wireless devices across multiple segments, e.g., healthcare, sports, child monitoring, military, emergency, consumer electronics, etc., is rapidly increasing. Multibillion wearable sensors are predicted to be in use by 2025, with over 30% of them being new types of sensors that are only beginning to emerge. This book will focus on wireless wearable and implantable systems, flexible textile-based electronics, bio-electromagnetics, antennas and propagation, radio frequency (RF) circuits, sensors, security of wearables and implantable systems, nano-bio communication, and electromagnetic sensing
English
Keywords: n/a; S-Band sensing; telerehabilitation; wavelet transform; WBAN; reservoir computing; rehabilitation; medical wearable wireless devices; energy efficiency; multiuser; wireless body area networks; echo state networks; electrocardiography (ECG); inertial sensor; heart beat classification; S-band sensing; patch ECG monitor; IMU; Unity; Chronic Obstructive Pulmonary Disease (COPD); cryptanalysis; ankle sprain; medical internet of things; wireless VR; Arduino; wireless channel information; bio signals; security; wearable electronic device; accelerometer; energy-balanced model; diversity combining; anonymity; OFDMA; bio sensors; hyperthyreosis/sleep apnea disease monitoring; SDPPG; medium access control; Internet of Things; Quality of Service; gyroscope; C-Band; movement noise; smart devices; wearable sensors; wireless LAN; Virtual Reality